The tumor-endothelium cell interaction in pioneering studies and the revisited concept on the angiogenesis process during tumor progression and metastasis - Rizzi, Manuela; Gallazzi, Matteo; Tosetti, Francesca; Mortara, Lorenzo (Medicina Historica, 2020)
The growth of solid tumors and their dissemination require the continuous formation of new capillary blood vessels. However, the association of uncontrolled growth of tumors and angiogenesis, i.e. the mechanism that allows the formation of new blood vessels starting from pre-existing vessels, dates back to 1971, in relation of Judah Folkman’s works. Since then, his group and other researchers added new key results confirming the important role played by angiogenesis in tumor growth and metastasis, and multiple efforts have been made to exploit this knowledge in developing innovative anti-cancer therapies. In this article, we discuss seminal works regarding molecular mechanisms involved in aberrant tumor angiogenesis, biology of endothelial cells within extracellular matrix, function of diverse pro- and anti-angiogenic factors, roles of metalloproteinases and pro-tumor effects played by stromal and immune cells in the tumor microenvironment. Interestingly, growing evidences indicate a key role played by inflammatory and stromal cells in both tumor development and progression. The present article also aim to provide up-to-date information concerning new therapeutic concepts involving tumor vessels normalization and anti-angiogenic agents, among which inhibitors of metalloproteinases and of the main angiogenic factor, vascular endothelial growth factor (VEGF) or its receptors, and the combination of them with immune checkpoint blockade, that seem to be the most promising ones at present.